Replication Report: The Welfare Effects of Pride and Shame - Tilman Fries (Institute for Replication (I4R), 2023)
This replication report examines and extends the research conducted by Butera, Metcalfe, Morrison, and Taubinsky (2022) on "The Welfare Effects of Pride and Shame." The original paper explores the welfare implications of public recognition as a motivator for desirable behavior and introduces an empirical methodology to measure Public Recognition Utility (PRU), which quantifies the utility individuals experience when their actions are publicly recognized. This report focuses on the real effort experiment reported in the paper that was conducted using a classroom sample, a lab sample, and an online sample. I computationally reproduce the original results and verify their robustness. While reproducing the results, I found two minor coding errors in the replication package. Correcting these errors slightly changes some estimates reported in the paper but does not turn over any results. The main treatment effect findings are further robust to using different sets of controls and sample selection criteria. Moreover, I conduct a heterogeneity analysis which reveals significant variations in how participants value public recognition. Overall, the replication study confirms the original conclusions while providing additional insights into the heterogeneity of PRU shapes on an individual level.
Keywords: 330